Management of patients with allergic diseases during pregnancy: lecture - S.V. Zaikov; A.Ye. Bogomolov; N.A. Hritsova; A.P. Grуshуlo (Civic Union "Communicable Diseases Intensive Care Association", 2022)
ABSTRACT. In connection with the considerable increase of prevalence of allergic diseases (AD) there all more often are situations, when it will be to decide the question of management of patients a doctor with an allergy during pregnancy. Prevalence of AD (allergic rhinitis/conjunctivitis, allergic phenotypes of bronchial asthma and hives, atopic dermatitis, food/drug/insect allergy, anaphylaxis) among pregnant women can arrive 30 %. It is possible to distinguish three types of influence of pregnancy on clinical motion of AD: 1) presence of pregnancy does not affect motion of AD; 2) on a background pregnancy comes remission of AD; 3) on a background pregnancy arise up intensifying of AD and their motion are burdened. It is difficult to predict exactly how the course of AD will occur during pregnancy, while the nature of treatment of a pregnant woman with AD and the level of their control are extremely important. At pregnancy diagnosis of AD is based on data of allergic anamnesis, food diary, physical inspection. Thus realization of skin and provocative tests with allergens contra-indicated. Application of provocative tests is also forbidden with a histamine, а methacholine and an acetylcholine. At treatment of pregnant from AD must be taken into account possible side effects of antiallergic drugs. Setting of modern medicinal facilities allows in most cases to control motion of allergic pathology for pregnant and avoid development of side effects of drugs. Treatment of AD during pregnancy the best result must provide for a mother and child. Medical workers must inform the women of reproductive age and pregnant of potential risks and present/absent proofs of unconcern/ununconcern of diagnostic and curative events.